2018
DOI: 10.1177/0022034518772260
|View full text |Cite
|
Sign up to set email alerts
|

Pulp Regeneration by 3-dimensional Dental Pulp Stem Cell Constructs

Abstract: Dental pulp regeneration therapy for the pulpless tooth has attracted recent attention, and clinical trial studies are underway with the tissue engineering approach. However, there remain many concerns, including the extended period for regenerating the dental pulp. In addition, the use of scaffolds increases the risk of inflammation and infection. To establish a basic technology for novel dental pulp regenerative therapy that allows transplant of pulp-like tissue, we attempted to fabricate scaffold-free 3-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
113
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 42 publications
1
113
0
2
Order By: Relevance
“…Herein, a biodegradable scaffold serves as a temporary matrix for regenerating cells to attach, proliferate, and differentiate to mature and functional cells which produce pulp and dentin. 18,19 It is now well-established that mesenchymal stem cells which migrate from different sources such as apical papilla, periodontal ligament, and bone marrow play a significant role in pulp and dentin regeneration. 20 In the present case, migrating stem cells are suggested to be responsible for pulp regeneration, dentin production, and root development.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Herein, a biodegradable scaffold serves as a temporary matrix for regenerating cells to attach, proliferate, and differentiate to mature and functional cells which produce pulp and dentin. 18,19 It is now well-established that mesenchymal stem cells which migrate from different sources such as apical papilla, periodontal ligament, and bone marrow play a significant role in pulp and dentin regeneration. 20 In the present case, migrating stem cells are suggested to be responsible for pulp regeneration, dentin production, and root development.…”
Section: Discussionmentioning
confidence: 71%
“…In the revascularization procedure, the clinician uses the approach of tissue engineering for the regeneration of pulp tissue and maturation of root apex. Herein, a biodegradable scaffold serves as a temporary matrix for regenerating cells to attach, proliferate, and differentiate to mature and functional cells which produce pulp and dentin . It is now well‐established that mesenchymal stem cells which migrate from different sources such as apical papilla, periodontal ligament, and bone marrow play a significant role in pulp and dentin regeneration .…”
Section: Discussionmentioning
confidence: 99%
“…There are several methods of fabricating 3D cell constructs, such as applying a low attachment cell culture plate, thermos‐responsive polymers, and the layer‐by‐layer technique . These methods represent easy ways of obtaining cell constructs; however, it is difficult to control the morphology of constructs obtained via these methods.…”
Section: Introductionmentioning
confidence: 99%
“…13 It has also been reported that cell interactions and drug sensitivities could be more accurately evaluated for anticancer drug development using cell constructs. 14 There are several methods of fabricating 3D cell constructs, such as applying a low attachment cell culture plate, 15 thermosresponsive polymers, 16 and the layer-by-layer technique. 17 These methods represent easy ways of obtaining cell constructs; however, it is difficult to control the morphology of constructs obtained via these methods.…”
Section: Introductionmentioning
confidence: 99%
“…Scaffold-free schemes using microtissues of various cell types in complex shapes such as spheroids, rods, toroids [5][6][7], and sheets not only facilitate a more in vivo-like environment for the transplanted cells but also avoid issues sprouting from inflammation and slow degradation of the scaffolds [8]. In order to mimic the rod-like shape of the root canal, attempts have been made to fabricate the most suitable cell-seeding system including sheets and spheroids [4,9]. The rationale behind our research was to check the feasibility of molding dental pulp cells into rodshaped microtissues and to investigate the potential signaling pathways responsible for regulating their contraction.…”
Section: Introductionmentioning
confidence: 99%